2010
DOI: 10.1128/jb.00539-10
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusNrdH Redoxin Is a Reductant of the Class Ib Ribonucleotide Reductase

Abstract: Staphylococci contain a class Ib NrdEF ribonucleotide reductase (RNR) that is responsible, under aerobic conditions, for the synthesis of deoxyribonucleotide precursors for DNA synthesis and repair. The genes encoding that RNR are contained in an operon consisting of three genes, nrdIEF, whereas many other class Ib RNR operons contain a fourth gene, nrdH, that determines a thiol redoxin protein, NrdH. We identified a 77-amino-acid open reading frame in Staphylococcus aureus that resembles NrdH proteins. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 49 publications
1
36
1
Order By: Relevance
“…In the presence of 1 to 2 mM dithiothreitol (DTT), TrxL significantly stimulated RNR activity (see Fig. S3 in the supplemental material), suggesting that in vivo it can function with thioredoxin reductase and NADPH as an electron donor for the aerobic class I RNR, in a manner similar to that of E. coli and S. aureus NrdH (39,45).…”
Section: Resultsmentioning
confidence: 92%
“…In the presence of 1 to 2 mM dithiothreitol (DTT), TrxL significantly stimulated RNR activity (see Fig. S3 in the supplemental material), suggesting that in vivo it can function with thioredoxin reductase and NADPH as an electron donor for the aerobic class I RNR, in a manner similar to that of E. coli and S. aureus NrdH (39,45).…”
Section: Resultsmentioning
confidence: 92%
“…As a comparison, the K m of E. coli TR for its NrdH (CVQC active site) is 2.5-fold lower (1.1 M), and the V max is 89% that for E. coli Trx1 (28). The previously published data for the more closely related NrdH from S. aureus does not permit a direct comparison, but the activity appears to be low (51). (5), whereas NrdH redoxins are restricted to bacteria and seem to be exclusively involved in reduction of class Ib RNRs (12).…”
Section: B Anthracis Genome Encodes Several Potential Thioredoxinmentioning
confidence: 83%
“…E. coli NrdH was found to give a K m of 0.3-0.6 or 1.2-1.6 M depending on whether the electrons were supplied by either DTT or TR/NADPH, whereas thioredoxin 1 was inactive (28). Aharonowitz and co-workers (51) found that both S. aureus NrdH and Trx1 were active as Table 1 and the E. coli proteins Trx1 and Trx2 plus Grx1-Grx4 were each subjected to -Blast, and the 200 top candidates after 6 -12 iterations were included in the comparison. In addition, all NrdH proteins listed in RNRdb were included prior to a ClustalX run with 1700 individual entries (after manual deletion of duplicates).…”
Section: Discussionmentioning
confidence: 99%
“…1) (2, 55). A number of artificial and endogenous systems are capable of mediating this re-reduction step, including dithiothreitol (DTT),Trx/TrxR/NADPH, Grx/ GSH/GR/NADPH, and NrdH/TrxR/NADPH, where Trx is thioredoxin, Grx is glutaredoxin, and GR is glutaredoxin reductase (6,11,20,21,56). The observation that nrdH is colocalized in the same operon with nrdE and nrdF in S. sanguinis and many other organisms makes this protein the most reasonable candidate for the endogenous reductant.…”
Section: Identification Of the Genes For Cluster Assembly And Activitmentioning
confidence: 99%
“…1) and thus is required for multiple turnovers (6,11,(17)(18)(19). NrdH itself can be re-reduced in vitro by TrxR and NADPH in E. coli, B. anthracis, Staphylococcus aureus, and Corynebacterium glutamicum (6,11,20,21).…”
mentioning
confidence: 99%